PENGARUH PERSEPSI PROFESI GURU DAN EFIKASI DIRI TERHADAP MINAT MENJADI GURU - Saniyatus Sholichah; Triesninda Pahlevi (Universitas Negeri Malang, 2021)
Abstract: This study aims to find the influence of perception of the teacher profession and self-efficacy on the interest of becoming a teacher in students of the Office Administration Education Study Program of the Faculty of Economics, State University of Surabaya Class of 2017. The type in this study is explanatory research with quantitative approach. The data is collected through research instruments using questionnaires. The analysis method is multiple linear regression analysis with SPSS 25 application. The results of the study were: (1) The perception of the teacher profession positively and significantly influenced the interest in becoming a teacher in students of education department of office administration unesa 2017. (2) Self-efficacy does not have a significant influence on the interest in becoming a teacher in students of unesa office administration education program 2017. (3) The perception of the teacher's profession and self-efficacy positively and significantly affect the interest of teachers in students of education department of office administration of UNESA 2017. Keywords: Perception of The Teacher's Profession; Self Efficacy; Interest Becoming a Teacher. Abstrak: Penelitian ini memiliki tujuan untuk mendapati pengaruh persepsi profesi guru dan efikasi diri terhadap minat menjadi guru pada mahasiswa Program Studi Pendidikan Administrasi Perkantoran Fakultas Ekonomi Universitas Negeri Surabaya Angkatan 2017. Jenis pada penelitian ini yaitu penelitian eksplanatori dengan pendekatan kuantitatif. Data dikumpulkan melalui instrument penelitian dengan menggunakan angket. Metode analisis yaitu analisis regresi linear berganda dengan aplikasi SPSS 25. Hasil penelitian yaitu: (1) Persepsi profesi guru berpengaruh secara positif dan signifikan terhadap minat menjadi guru pada mahasiswa prodi pendidikan administrasi perkantoran UNESA 2017. (2) Efikasi diri tidak memberikan pengaruh yang signifikan terhadap minat menjadi guru pada mahasiswa prodi pendidikan adminitrasi perkantoran UNESA 2017. (3) Persepsi profesi guru dan efikasi diri berpengaruh secara positif dan signifikan terhadap minat mnejadi guru pada mahasiswa prodi pendidikan administrasi perkantoran UNESA 2017. Kata kunci:Persepsi Profesi Guru; Efikasi Diri; Minat Menjadi Guru.